POLA AKTIVITAS, KONSUMSI PANGAN, STATUS GIZI DAN KESEHATAN ANAK JALANAN DI KOTA BANDUNG - Nur'aini Nur'aini; Mira Dewi (Food and Nutrition Society of Indonesia, 2009)
The objective of the research was to analyze activity pattern, dietary consumption, nutritional status and health of street children in Bandung. Cross sectional design was used in this study to elaborate activity pattern, food consumption, nutritional status and health of street children in Bandung. Samples of street children was recruited by purposive sampling from eight NGOs in Bandung with following criterias: 1) 5-18 years old 2) spend time on the street at least four hours a day 3) work for living on the street, commonly as singers, beggars, shoe-polisher, porters etc. The result showed that most of the street children worked as singers, spend 4-8 hours a day and 4-6 days a week. The average energy and protein adequacy level of street children was in light deficit category, iron and vitamin Cwere in low category and vitamin A was in sufficient category. Almost all of the street children had normal nutritional and health status and good personal hygiene. There was no correlation between activity and duration of street children with nutrition adequacy level. There was no correlation between personal hygiene and nutritional status with health status.